The role of organizational trust dimension in customer relationship management: Applied research in the general ethnic insurance company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               The aim of the research is to verify the role of organizational trust as an “administrative” dimension of objective importance in the relationships adopted by the Iraqi General Insurance Company with customers, as it is one of the basic pillars in building and succeeding companies, which allows the provision of services with high confidence through the customer relationship management system in order to achieve The company's goal is to gain new customers, retain current customers, increase work in insurance companies, and develop the national economy by increasing the company's sales and profitability. The research adopted statistical methods, as (300) questionnaires were distributed to employees of the company under investigation. (282) were retrieved. A questionnaire suitable for statistical analysis, in addition to conducting personal interviews with managers and officials of the surveyed company. This study relied on the descriptive analytical approach. The most prominent results that the research reached are that there is a strong moral correlation between the dimension of trust and customer relationship management.